Perkembangan Bank Syariah Di Asia Tenggara: Sebuah Kajian Historis - Ghozali, Mohammad; Azmi, Muhammad Ulul; Nugroho, Wahyu (Falah: Jurnal Ekonomi Syariah, 2019)
The development of Islamic Banking in Southeast Asia is growing rapidly. Statistical data shows that Southeast Asia has become one of the centers for the development of the global Islamic finance industry. Literally, Indonesia and Malaysia is two countries in the region that have become dynamos for the development of the Islamic banking industry in ASEAN countries, this condition has encouraged other countries to be discussed in the development of the Islamic banking industry. The method of this paper is historical approach, which documentary methods in data collection techniques by analyzing documents that are relevant to the research topic. The conclusion of this study is that significant developments still occur in two countries, namely Malaysia and Indonesia, whereas in some countries such as Thailand, Singapore and the Philippines the development of Islamic banking is still minimal.